2015
DOI: 10.1097/mnm.0000000000000254
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of preoperative 18F-FDG PET for histopathological differentiation and early recurrence of primary malignant intrahepatic tumors

Abstract: A preoperative 18F-FDG PET scan can be considered a useful reference for postoperative tumor recurrence and histopathological differentiation in cases of primary malignant intrahepatic tumors. 18F-FDG PET scan results should be interpreted separately for malignant liver tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 45 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…In BTCs, studies about the issues are limited. Preoperative metabolic activity in BTCs was associated with recurrence risk and survival outcome (12,13). In the metastatic setting, Kitamura et al showed that SUV max was associated with OS; however, this study included only patients with EHCC and evaluated only the metabolism at the primary tumor site (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In BTCs, studies about the issues are limited. Preoperative metabolic activity in BTCs was associated with recurrence risk and survival outcome (12,13). In the metastatic setting, Kitamura et al showed that SUV max was associated with OS; however, this study included only patients with EHCC and evaluated only the metabolism at the primary tumor site (14).…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing on the tumor metabolism of BTCs are limited, and a small number of the studies are mostly retrospective data and have some barriers to the clinical application (12)(13)(14)(15)(16). We previously reported that the tumor metabolism of BTC assessed by 18 F-FDG PET before chemotherapy had a prognostic value identified by retrospective analysis (17).…”
mentioning
confidence: 99%
“…In multimodality treatment, chemotherapy can control micrometastasis as well as play the role of a radiosensitizer (30). Because HCCs with aggressive features and rapid tumor growth show high 18 F-FDG uptake (15,31), the efficacy of multimodality treatment might be more prominent in patients with a high 18 F-FDG uptake than that of monotherapy. This hypothesis may explain why patients treated with CCRT, a multimodality treatment, had better PFS and OS than those with TACE as a monotherapy, particularly among patients with a high 18 F-FDG uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Positron-emission tomography (PET) seems to be a more effective and noninvasive modality than traditional radiography techniques for scanning the whole body[8]. Although 2-deoxy-2-( 18 F)fluoro-D-glucose ( 18 F-FDG) PET has a low sensitivity, between 36% and 70%, in detecting HCC[9-11], the application of PET-CT for diagnosing HCC has made great progress in recent years. This review presents an overview of the current status and future prospects of PET for diagnosing HCC.…”
Section: Introductionmentioning
confidence: 99%